ADVERSE EFFECTS OF PYRAZINAMIDE IN PAKISTANI PATIENTS - Zaman, Ronaq; Orakzai, Shaukat Ali (Journal of Ayub Medical College Abbottabad, 1988)
Abstract: The effect of Pyrazinamide on Liver and Kidney function tests as well as on Serum and Urinary Uric Acid levels was studied in Patients with Pulmonary Tuberculosis. A rise in Serum total and direct bilirubin, SGOT and SGPT was observed. No significant rise was observed in alkaline phosphatase concentration. One out of fifteen patients developed Jaundice. A rise in Serum Uric Acid, Serum Creatinine concentration during drug therapy was associated with a fall in Urinary Excretion of Uric Acid and Creatinine.